(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In the current years, social media became one of the most important sources of data fordifferent data analytic purposes. One of the most important issues is how to map different trends insocial media and define the relation between different groups based on their sentiment or interests. SA,recommendation systems, event tracking, summarization, etc. all rely heavily on it as a component ofNLP. The proliferation of social media platforms, the ease with which users can maintain a constantonline presence, rise of Web 2.0 have all contributed to a meteoric rise in the volume of digital socialmedia data. Microblogging sites like Twitter, blogs, review collection websites, online forums have beencontributing to the large scale of big data.